A tribological comparison of pure and boronized chromium - Ribeiro, R.; Ingole, S.; Usta, M.; Bindal, C.; Ucisik, A. H.; Liang, H. (Asme, 2006)
Boronized metals are potential candidate materials for various industrial applications as well as for joint arthroplasty. This is due to their high hardness and corrosion resistance. In the present research, we investigated the tribological performance of boronized chromium when worn against bearing steel E52100. Pure chromium was used as a control material and tested under similar conditions. Three test conditions were used-dry sliding, with water and with simulated body fluid (SBF). The highest coefficient of friction obtained was for chromium boride under dry sliding conditions. Water and SBF acted as lubricants and lowered the coefficient of friction. The friction coefficient for Cr and chromium boride was lowest under SBF conditions. SEM analysis showed that the wear modes were different under different test conditions. TEM analysis showed a layered-like structure of debris that could have acted as a lubricant and caused a very low friction coefficient as the tests progressed.
Keywords: coating; wear debris; simulated body fluid; friction